Psychophysiology of violence: aspects of ethology and Society - Beteta Pacheco, Edmundo (1999)
In order to study the biological factors of violence, it is presented the neurobiological research of agression in man and animals. We discuss the controversial aspects of the ethology and the social anthropology. Al the end, the interpretation of social violence should be done taking on account the psychobiological factors. Unfortunately the research about violence in Peru, it did not look for the biological aspects of this problem.